2005
DOI: 10.1091/mbc.e05-02-0171
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase C2α Is Essential for ATP-dependent Priming of Neurosecretory Granule Exocytosis

Abstract: Neurotransmitter release and hormonal secretion are highly regulated processes culminating in the calcium-dependent fusion of secretory vesicles with the plasma membrane. Here, we have identified a role for phosphatidylinositol 3-kinase C2␣ (PI3K-C2␣) and its main catalytic product, PtdIns3P, in regulated exocytosis. In neuroendocrine cells, PI3K-C2␣ is present on a subpopulation of mature secretory granules. Impairment of PI3K-C2␣ function specifically inhibits the ATP-dependent priming phase of exocytosis. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 62 publications
5
108
0
Order By: Relevance
“…It was shown that synapsin1-associated PI-3K regulates the size of the ready-releasable pool of synaptic vesicles [32]. Considering the essential role of PI-3K in ATP-dependent priming [59] and that PI-3K inhibitors can compete with PIP for the kinase ATP-binding site [81,95], inhibition of fusion extent seen here (Figs. 8a, b and 9a, b) is likely caused by CV depriming in the fully docked state.…”
Section: Roles For Polyphosphoinositides In Regulated Releasesupporting
confidence: 53%
See 2 more Smart Citations
“…It was shown that synapsin1-associated PI-3K regulates the size of the ready-releasable pool of synaptic vesicles [32]. Considering the essential role of PI-3K in ATP-dependent priming [59] and that PI-3K inhibitors can compete with PIP for the kinase ATP-binding site [81,95], inhibition of fusion extent seen here (Figs. 8a, b and 9a, b) is likely caused by CV depriming in the fully docked state.…”
Section: Roles For Polyphosphoinositides In Regulated Releasesupporting
confidence: 53%
“…Considering the suggested roles of PIP species in exocytosis [5,36,59, 63], we studied their possible functions in Ca 2+ -triggered fusion. Eggs were treated with Wrt and LY29 to down-regulate PI-3K activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI(3)P, synthesized by PI3KC2α on chromaffin granules, positively regulated secretion (Meunier, Osborne et al 2005;Wen, Osborne et al 2008). However, PI(3)P turnover and/ or PI conversion was not addressed by this study.…”
Section: Pi Conversion In Endosomal Exocytosis Parallels Switching Ofmentioning
confidence: 74%
“…Chromaffin cells were isolated from bovine adrenal glands 48,49 and maintained in Dulbecco's modified Eagle's medium supplemented with 10% serum supreme, 2.5 mg ml À 1 fungizone, 50 mg ml À 1 gentamycin and 10 mM HEPES on 0.1 mg ml À 1 poly-D-lysine-coated culture dishes (MatTek Corporation). Cells were transfected using electroporation (Amaxa Basic Nucleofector Kit for primary neurons (Lonza), Program X-001) and cultured at 37°C/5% CO 2 for at least 24 h before experimentation.…”
Section: Methodsmentioning
confidence: 99%